2008
DOI: 10.1016/j.jana.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing HIV and Intimate Partner Violence Prevention Modules Among Spanish-Speaking Latinas

Abstract: The purpose of this study was to test two modules of a theoretically based, gender- and culturally specific HIV intimate partner violence risk reduction intervention for Spanish-speaking Latinas. The themes of the modules were "Estás en una relación sana y segura?" (Are you in a healthy and safe relationship?) and "Mantenerse sana y segura" (Keeping yourself healthy and safe). An evaluative one-group, repeated measure design with measures collected at preintervention (N = 31), immediate postintervention (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Two studies showed promising results with respect to the prevention of IPV [48,79], though not of incident HIV infection, and one showed promising results in terms of attitudes toward and intention to perform HIV-IPV risk reduction behaviours [113]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies showed promising results with respect to the prevention of IPV [48,79], though not of incident HIV infection, and one showed promising results in terms of attitudes toward and intention to perform HIV-IPV risk reduction behaviours [113]. …”
Section: Resultsmentioning
confidence: 99%
“…A pilot study of an HIV-IPV risk reduction intervention for Spanish-speaking Latinas was conducted in Detroit, Michigan, USA with 31 women [22]. The intervention consisted of two modules with the underlying themes “Are you in a healthy and safe relationship?” and “Keeping yourself healthy and safe,” and small group discussions related to HIV-IPV informational decision making and skills building activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several behavioral HIV prevention studies included violence prevention content, only a handful of interventions addressed these complex relationships by including changes in violence measures as a primary endpoint or by recruiting survivors of violence as the study population. 12,53,7077 …”
Section: Discussionmentioning
confidence: 99%
“…A few small feasibility studies (e.g., Davila et al, 2008; Enriquez et al, 2010) have described interventions that provide information about partner violence in the context of HIV prevention for non justice-involved women. One large study recruited women who were judged to be at risk for HIV and partner violence by virtue of being justice involved (i.e., recently incarcerated, or on parole or probation; Weir et al, 2009).…”
mentioning
confidence: 99%